Komentarz do przekładów literatury polskiej w Macedonii w 2016 roku - Tanuševska, Lidija (Wydawnictwo Uniwersytetu śląskiego Katowice, 2017)
There were only six instances of literary translation from Polish into macedonian in 2016. Some of them represent the genre of Polish literary reportage, but all of them represent a strong connection to the real facts of life. it seems that the choice is made based on the criteria imposed by the foundations partially commissioning the translation, but also shifting political situation in the country and the curiosity of the foreign reality. Translation problems appear to be of different nature, depending on the style of the author.
Keywords: реалност, превод, наратив, јазик, стил